THE COMPETENCE OF HONORARY BOARD OF THE GENERAL ELECTIONS TO AMEND THE DECISION OF THE GENERAL ELECTION COMMISSION OF THE PROVINCE OF EAST JAVA (A Case Study on the Decision NO. 74/DKPP-PKE-II/2013) - Sekartadi, Lalu Kukuh (Jurnal IUS, 2015)
The research aims to study the standing of the Honorary Board of The General Elections within the execution of the general election and the legal force of the decision of the Honorary Board of The General Elections to revise and annul the decision of the Honorary Board of The General Elections of the Province of East Java. This is a normative research. It applies statutory, conceptual and case approach. It also uses primary, secondary and tertiary legal materials. To collect legal materials, it employs literature study and furthermore is organized descriptively and analyzed qualitatively. The research shows that the standing of the Honorary Board of The General Elections parallel with the general elections commission and supervision board of general election, where the general elections commission and supervision board of general election are the executor of general elections, and the Honorary Board of The General Elections is assigned to enforce the code of conduct of the executors of general elections themselves. The legal force of decision of the Honorary Board of The General Elections is binding and executable and therefore there is no legal remedy can be taken by the party found guilty of disobeying code of conduct. Yet, in the other hand, control and clear rules in other that the Honorary Board of The General Elections can perform its duties in accordance with its function and authority consistently. Keywords: the Honorary Board of The General Elections, the General Elections Commission, the Supervision Board of General Elections.